Wives’ Work Idle Among Padi-Farming Households in Two Villages in Malaysia - Dagoy, Fe J. (1989)
The main purpose of this study was to determine wives' work role among padi -farming households in two villages in Malaysia. The specific objectives were: a) to ascertain wives' home and farm work roles, b) to determine the factors related wives' home and farm work roles, and c) to determine wives' satisfaction in their home and farm work roles. were Data collected from 101 wives of padi farming households analyzed using the following SPSSX subprograms: Frequencies, Crosstabs, Reliability, T-test and Regression. The findings of the study were: 1. The amount and degree of work participation among wives of padi farming households were concentrated to home and childcare tasks.